HUBUNGAN PENGETAHUAN IBU DENGAN PENCEGAHAN CA MAMAE DI PUSKESMAS PEMBANTU TAMBUNAN WILAYAH KERJA UPT PUSKESMAS TANDANG BUHIT KECAMATAN BALIGE KABUPATEN TOBA SAMOSIR TAHUN 2017 - Tiarnida Nababan (Jurnal Maternitas Kebidanan, 2018)
Breast cancer is a global isseue and important international issue, because it is the most common degenerative disease in women in developed countries. Breast care regularly to detect breast abnormalities. Immediately perform breast examination if you feel less comfortable in the breast. Immediate treatment will provide hope for better recovery and life expectancy in breast cancer in detected early on. The purpose of this research is to identify correlation between mother’s knowledge and prevention of Ca Mamae at Tambunan Heath Center Working Area of Tandang Buhit Healt Unit of Balige District, Toba Samosir Regeancy in 2017. This type of research is an analytic survey with cross sectional design. The population in this research is all the mother who come check their health in work area Puskesmas Tandang Buhit Unit of Balige District as many as 38 people. The sampling technique in this research is determined by total sampling technique as many 38 people. The result of chi square test based on the degree of significance was (α) = 0,05 and df = 1 and the calculation result showed that X2 count 13,246 > X2 table 3,841. It can be conclude Ho was rejected. Ha was accepted. The conclusion of the research stated that there is a correlation between mother’s knowledge with prevention od Ca mamae at Tambunan Heath Center Working Area of Tandang Buhit Healt Unit of Balige District, Toba Samosir Regeancy in 2017. It is expected that respondents can be oped and apply healthy lifestyle, health diet, avoid alcohol and stress as an efford to prevent breast cancer.